Pre-steady-state Kinetic Analysis of Amino Acid Transporter SLC6A14 Reveals Rapid Turnover Rate and Substrate Translocation - Shi, Yueyue; Wang, Jiali; Ndaru, Elias; Grewer, Christof (Frontiers in Physiology, 2021)
SLC6A14 (solute carrier family 6 member 14) is an amino acid transporter, driven by Na+ and Cl- co-transport, whose structure, function and molecular and kinetic mechanism have not been well characterized. Its broad substrate selectivity, including neutral and cationic amino acids, differentiates it from other SLC6 family members, and its proposed involvement in nutrient transport in several cancers suggest that it could become an important drug target. In the present study, we investigated SLC6A14 function and its kinetic mechanism after expression in human embryonic kidney (HEK293) cells, including substrate specificity and voltage dependence under various ionic conditions. We applied rapid solution exchange, voltage jumps and laser photolysis of caged alanine, allowing sub-millisecond temporal resolution, to study SLC6A14 steady state and pre-steady state kinetics. The results highlight the broad substrate specificity, and suggest that extracellular chloride enhances substrate transport, but is not required for transport. As in other SLC6 family members, Na+ binding to the substrate-free transporter (or conformational changes associated with it) is electrogenic, and is likely rate limiting for transporter turnover. Transient current decaying with a time constant of < 1 ms is also observed after rapid amino acid application, both in forward transport and homoexchange modes, indicating a slightly electrogenic, but fast and not rate-limiting substrate translocation step. Our results, which are consistent with kinetic modeling, suggest rapid transporter turnover rate and substrate translocation with faster kinetics compared with other SLC6 family members. Together, these results provided novel information on the SLC6A14 transport cycle and mechanism, expanding our understanding of SLC6A14 function.